Figurative Language Use in Song Lyrics in English Textbook Senior High School - Serefina Veronika Ketaren; Susi R. Sipahutar; Elen Magdalena Marpaung; Erikson Saragih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to determine the types of figurative language in song lyrics in English textbooks and determine the types of figurative language most often used in song lyrics. In this research, the researchers used a qualitative method. Researchers used data collection documentation techniques. In analyzing the data, the researchers classified the figurative language data based on Perrine’s theory. The researchers found four types of figurative language in the song 'Pathway to English,' namely, metaphor, simile, hyperbole, and metonymy. The variety of figurative languages most used is hyperbole. By using figurative language, the writer can also express their feelings to convey the song's meaning. Keywords: Figurative Language, Song Lyrics, English Textbook